Academic word list knowledge of Malaysian ESL undergraduates - Nur Ainil Sulaiman,; Khazriyati Salehuddin,; Rozainee Khairuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Academic words are specialised vocabulary of academic texts. The knowledge of these words is vital for comprehension and communication purposes, particularly among university students, to enable them to engage with authentic complex input, such as textbooks and journal articles. Limitation of academic vocabulary in their mental lexicon may restrict students ‘comprehension to grasp the academic concepts they are learning. The current study investigated Malaysian English as a Second Language (ESL) undergraduates’ knowledge of academic words, based on Coxhead’s (2000) Academic Word List (AWL). The AWL consists of academic words commonly used in academic texts across four general disciplines of studies namely arts, commerce, law, and science. The list consists of 570 word families categorised in 10 sub lists based on frequency and range. One hundred and eleven first year undergraduates with different levels of English language proficiency and from different academic disciplines at a research university in Malaysia participated in this study. Data were collected using a questionnaire, which comprised a list of words derived from the AWL. Findings show that AWL words from sub lists 8 until 10 (which consist of low frequency and low utility academic words) had the highest percentage of unknown AWL words reported by students compared to the other sub lists. The distributions of unknown academic words reported were also different among students with regards to their academic disciplines and English language proficiency. Although the findings in general are rather evident, identifying unknown academic word among undergraduates from different academic programmes is significant to instructors and learners so as to enable them to focus on the right words during valuable class and independent study time.